2013
DOI: 10.1371/journal.ppat.1003169
|View full text |Cite
|
Sign up to set email alerts
|

flp-32 Ligand/Receptor Silencing Phenocopy Faster Plant Pathogenic Nematodes

Abstract: Restrictions on nematicide usage underscore the need for novel control strategies for plant pathogenic nematodes such as Globodera pallida (potato cyst nematode) that impose a significant economic burden on plant cultivation activities. The nematode neuropeptide signalling system is an attractive resource for novel control targets as it plays a critical role in sensory and motor functions. The FMRFamide-like peptides (FLPs) form the largest and most diverse family of neuropeptides in invertebrates, and are str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…In a sand column motility assay, knockdown of Gp - flp-1 and 18 and flp-6, 12 , and 14 inhibited motility of second-stage juvenile (J2) Globodera pallida animals by 70–100% after 24 h of dsRNA soaking; the effects were transitory and by 6 days post-treatment, 27.1% of the animals recovered 39.4% of their normal activity ( 133 ). By contrast, when Gp - flp-32 was knocked down, G. pallida and Meloidogyne incognita juveniles became more mobile, which translated to an enhanced ability to infect potato plant and other plant roots ( 135 ).…”
Section: Diversity Of Flps In Nematodesmentioning
confidence: 99%
“…In a sand column motility assay, knockdown of Gp - flp-1 and 18 and flp-6, 12 , and 14 inhibited motility of second-stage juvenile (J2) Globodera pallida animals by 70–100% after 24 h of dsRNA soaking; the effects were transitory and by 6 days post-treatment, 27.1% of the animals recovered 39.4% of their normal activity ( 133 ). By contrast, when Gp - flp-32 was knocked down, G. pallida and Meloidogyne incognita juveniles became more mobile, which translated to an enhanced ability to infect potato plant and other plant roots ( 135 ).…”
Section: Diversity Of Flps In Nematodesmentioning
confidence: 99%
“…Urwin et al (2002) demonstrated that octopamine, a neuro active stimulant, could stimulate the oral uptake of dsRNA. Following this approach, investigation of FLP gene function through RNAi has been well documented for some key plant-parasitic nematodes (Urwin et al, 2002;Kimber et al, 2007;Dalzell et al, 2009;Atkinson et al, 2013). In vitro RNAi silencing of the two neuropeptide genes, flp-12 and flp-18, reduced the migration of J2 of M. incognita in a sand column (Dalzell et al, 2010).…”
mentioning
confidence: 99%
“…One application of com parative genomic analysis has already revealed that the ge netic bases of developmental arrest in C. elegans and H. glycines differ significantly (Elling et al, 2007), provid ing important guidance for analysis of development. The area of nematode neuropeptides and their application for nematode control has flourished with a foundation in C. elegans genetics (Li, 2005;Li & Kim, 2010) and the co operation amongst those investigating the genetics, phys iology and biochemistry of these regulatory molecules in free-living, plant-parasitic and animal-parasitic nema todes (McVeigh et al, 2008(McVeigh et al, ,2012Holden-Dye & Walker, 2011;Maule & Curtis, 2011;Atkinson et al, 2013).…”
Section: Resultsmentioning
confidence: 99%